If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(a + 2) + -9(a + 9) = -4(2a + 9) + -16 Reorder the terms: 4(2 + a) + -9(a + 9) = -4(2a + 9) + -16 (2 * 4 + a * 4) + -9(a + 9) = -4(2a + 9) + -16 (8 + 4a) + -9(a + 9) = -4(2a + 9) + -16 Reorder the terms: 8 + 4a + -9(9 + a) = -4(2a + 9) + -16 8 + 4a + (9 * -9 + a * -9) = -4(2a + 9) + -16 8 + 4a + (-81 + -9a) = -4(2a + 9) + -16 Reorder the terms: 8 + -81 + 4a + -9a = -4(2a + 9) + -16 Combine like terms: 8 + -81 = -73 -73 + 4a + -9a = -4(2a + 9) + -16 Combine like terms: 4a + -9a = -5a -73 + -5a = -4(2a + 9) + -16 Reorder the terms: -73 + -5a = -4(9 + 2a) + -16 -73 + -5a = (9 * -4 + 2a * -4) + -16 -73 + -5a = (-36 + -8a) + -16 Reorder the terms: -73 + -5a = -36 + -16 + -8a Combine like terms: -36 + -16 = -52 -73 + -5a = -52 + -8a Solving -73 + -5a = -52 + -8a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '8a' to each side of the equation. -73 + -5a + 8a = -52 + -8a + 8a Combine like terms: -5a + 8a = 3a -73 + 3a = -52 + -8a + 8a Combine like terms: -8a + 8a = 0 -73 + 3a = -52 + 0 -73 + 3a = -52 Add '73' to each side of the equation. -73 + 73 + 3a = -52 + 73 Combine like terms: -73 + 73 = 0 0 + 3a = -52 + 73 3a = -52 + 73 Combine like terms: -52 + 73 = 21 3a = 21 Divide each side by '3'. a = 7 Simplifying a = 7
| -8+9+(-4)+6= | | x^3=-31 | | 5.6-0.221= | | 2*a-5=12 | | 8.4-(-6.5)= | | 24-5*a=15 | | y+1=30 | | (2x)2+x=3 | | 7x-1+117=180 | | 69-4x=14x+19 | | 7p-14=-17+4p | | 2t-18=-11+t | | 3(x-4)2-8=4 | | 2a-7=2(a+1)+9a+1 | | 8-4k=23-3k | | 2(x+5)=-3(x-30) | | -9x-18=-153 | | 12(x+5)=-3(x+30) | | 2/9n=8 | | 4x(x-3)=3x-8 | | -4/7r=-8 | | -4/9t=-8 | | y^2-20y+100=6x | | 23x-450=18x+175 | | p-47=36 | | -5-24=15 | | x+0,1/0,1=10 | | 4v^2-19v-5=0 | | 12/2=48/t | | 21-1=9x-57 | | 34/9=136/x | | 34/9=138/x |